Married Women's Decision‐Making Power on Family Planning Utilization and Associated Factors Among Married Women in Jeldu District, Ethiopia: An Implication for Women Empowerment - Yonas Tesfa Negasa; Elias Teferi; Jiregna Darega; Lencho Kajela Solbana (Health Science Reports)
ABSTRACT Background The increased usage of family planning is positively impacted by women's decision‐making authority. Thus, the purpose of this study was to ascertain the extent of married women's decision‐making authority about the use of family planning and the elements that are related to it. Methods A quantitative study supplemented by a qualitative cross‐sectional study was used to gather data from 606 married women in Jeldu District, Ethiopia between September 30, 2022, and October 30, 2022. The quantitative data were gathered using structured questionnaire and focused group discussion guide was used for the qualitative survey. Systematic random sampling was used to select the quantitative survey respondents where as purposive sampling was used to select focused group discussion participants. For analysis, the gathered data were imported into EpiData version 3.1 and exported to SPSS version 20. To identify the factors associated with decision‐making power on family planning utilization, binary and multivariable logistic regression analysis, 95% confidence interval and p value of less than 0.05, were used. Results Among the married women, 69.2% (CI 67%, 74%) reported having decision‐making power over the use of family planning. The study indicated that age > 40 years [AOR: 7.11, 95% CI: 2.31, 21.89], inability to read and write [AOR = 0.23, 95% CI: 0.12, 0.46], lack of information on family planning utilization during the ANC [AOR 0.23, 95% CI 0.10, 0.53], and non‐user of family planning during the study period [AOR: 0.29, 95% CI: 0.18, 0.46]. Conclusion The results of this study show that married women's decision‐making power regarding the use of family planning was generally poor. The decision‐making power on the use of family planning was substantially associated with age, educational attainment, health knowledge, and existing family planning usage. Therefore, it is advised to increase women's decision‐making power on family planning utilization by teaching them about their rights and bringing health services closer to the community.